Spores of microorganisms. XXVI. Synthetic activities of germinating spores of Bacillus cereus prevented from outgrowth - Stastná, J; Vinter, V (Folia microbiologica, 1975)
Spores of Bacillus cereus were germinated in a germination limited medium (GL-medium) which facilitates only germination but not the postgerminative development of spores. Under these conditions a limited protein synthesis occurs. However, this protein synthesis is stopped after a short time interval. The rate of synthesis of new proteins, as well as their total amount, is influenced by the length of the activation heat shock. Synthesis of the wall material continues for several hours and thick-walled cells with a changed ultrastructure are formed. Synthesis of the diaminopimelic acid (dap) containing material of the cell wall is sensitive to actinomycin D and relatively resistant to chloramphenicol. Similarly, protein synthesis is relatively chlorapmhenicol-resistant but is fully inhibited by azauracil or spiramycin. Whereas RNA formed in the control culture is partially decomposed after 30 min of incubation, chloramphenicol accelerates its synthesis and prevents its decay. Exudate components apparently stimulate synthesis of ribonucleic acid, proteins and the wall material. The 14-C-dap containing material released by prelabelled spores in the form of the exudate during the germination is not re-utilized by the spores germinated in the GL-medium. The results are discussed with respect to the atypical primary synthetic activities of spores under conditions when the postgerminative development is prevented and from the point of view of participation of the germination exudate during these syntheses.
Keywords: Protein Precursors; Leucomycins; Kinetics; daktinomycin; bakteriální proteiny; Bacterial Proteins; bakteriální RNA; chloramfenikol; Spores, Bacterial; Dactinomycin; Culture Media; proteinové prekurzory; uracil; kultivační média; RNA, Bacterial; buněčná stěna; Uracil; Chloramphenicol; Bacillus cereus; leukomyciny; spory bakteriální; kinetika; Cell Wall